Bizarre Parosteal Osteochondromatous Proliferation (Nora’s Lesion) of the Mandible. A Rare Bony Lesion - Dashti, H. M. (Springer US, 2011)
Bizarre parosteal osteochondromatous proliferation (BPOP) also eponymically called “Nora’s lesion”, is a rare benign reactive bone lesion first reported in 1983. BPOP occurs classically on the bones of the hands and feet and long bones. This lesion can easily be confused, both clinically and microscopically, with other benign and malignant lesions of bone, including osteochondroma, parosteal osteosarcoma, myositis ossificans and reactive periostitis. BPOP has been reported to have a high rate of recurrence. Only 3 cases of BPOP of the head and neck have been reported in the literature, of which one involved the maxilla. We present a rare case of BPOP involving the mandible in a 10 year old African American male. Microscopically, a fibro-cartilaginous cap giving rise to a proliferation of variably mineralized osteophytic finger-like projections of bone was seen. Multiple trabeculae of “blue bone” were noted as well as numerous atypical appearing chondrocytes. The lesion recurred within 4 months following the initial excision but has not recurred to date after the second local excision. To the best of our knowledge, this is the first report of BPOP arising in the mandible. In addition, we discuss the clinical and microscopic features, differential diagnosis, and prognosis of this rare entity. We present a case of BPOP of the mandible and believe this is the first report of such a case in the mandible.